Azure data scientist associate certification guide : a hands-on guide to developing machine learning skills and passing the Microsoft certified DP-100 exam /: a hands-on guide to developing machine learning skills and passing the Microsoft certified DP-100 exam. (2021) - Botsikas, Andreas; Hlobil, Michael
No abstract available